Pemanfaatan Bahan Lokal Sebagai Pestisida Nabati Untuk Mengendalikan Hama Ulat Spodoptera frugiperda Pada Tanaman Jagung - Yonce Melyanus Killa; Mersi Mandaha; Nelson A Raga; Suryani KKL Kapoe (Universitas Lambung Mangkurat, 2026)
Spodoptera frugiperda is one of the pests that persistently exist and damage plants. One alternative to control this pest is by using vegetable-based pesticides. The purpose of this study is to test the effect of vegetable pesticides made from local ingredients (srikaya seeds and soursop seeds) in controlling S. frugiperda caterpillar pests on corn plants. Hopefully, this information can help the community in pest management. This research was conducted in December 2023 at the Integrated Mathematics and Natural Sciences Laboratory of Wira Wacana Sumba Christian University. The study uses a completely randomized design (CRD) with 4 treatments and 4 replicates. The treatments were P0 (no vegetable pesticide), P1 (10% vegetable pesticide extract), P2 (20% vegetable pesticide extract), P3 (30% vegetable pesticide extract). The results showed that vegetable pesticide extracts from srikaya and soursop seeds significantly affected feeding activity but had no significant effect on pest mortality. The highest pesticide effect was observed in P3, with 100% pest reduction on day three. Treatments affecting feeding activity, especially in P3, resulted in about 43% food consumption.